Teaching public administrators and leaders to handle complexity - Raisio, Harri; Puustinen, Alisa; Vartiainen, Pirkko; Lindell, Juha; Ollila, Seija (University of Bamberg Press, 2018)
Understanding and working under complexity has become ‘the new normal’ in public administration. Hence complexity must also be integrated into teaching and training of public administrators, not only in higher education but also in in-service training and educating wider society. This can be done by combining the ongoing research agenda into courses and teaching methods. This article describes the integration of complexity thinking and teaching in one university, both by giving examples on the courses and methods applied, student feedback received and by anticipating future developments. Finally, practical advice for teachers of complexity is given.
Keywords: complexity; wicked problems; public administration; curriculum; higher education; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|